Robust Preimplantation Genetic Testing of Huntington Disease by Combined Triplet-Primed PCR Analysis of the HTT CAG Repeat and Multi-Microsatellite Haplotyping - Zhao, M. (Nature Publishing Group, 2021)
10.1038/s41598-019-52769-3